Analyzing TikTok Videos as Digital Resources for Developing EFL Speaking Skills: A Qualitative Content Study - Sara Laila Fatimah; Bambang Ruby Sugiarto; Leni Irianti (Universitas Galuh, 2026)
Speaking English is a crucial part of learning English as a foreign language (EFL), yet many Indonesian students struggle with vocabulary, grammar, pronunciation, and fluency. While numerous studies have been conducted on mobile-assisted language learning (MALL), little is known about the precise function of TikTok videos as a self-help tool for speaking acquisition, particularly in studies that do not consider the user's perspective. This study examines how TikTok videos can help improve English speaking skills, with an emphasis on vocabulary, grammar, pronunciation, and fluency. Three TikTok videos were selected using a qualitative content study. The results indicate that these videos demonstrate authentic and spontaneous English speaking techniques that can help users improve their speaking skills through unstructured digital content. This implies that TikTok videos can be used as supplementary speaking examples for students learning English as a second language (EFL). Teachers and content producers can learn more about the educational potential of social media platforms from this research.